Urinary c-peptide and urine C-peptide/creatinine ratio (ucpcr) are possible predictors of endogenous insulin secretion in t2dm subjects - a randomized study - KULKARNI C M,; SUMANGALA PATIL, (International Journal of Pharma and Bio Sciences, 2016)
Estimation of serum C-peptide (SCP) is used as a measure of endogenous insulin secretion in type 2 diabetes mellitus (T2DM). Urinary C- Peptide (UCP) and urinary C-Peptide creatinine ratio (UCPCR) are non invasive, simple and easily reproducible tests which may be considered as an alternative for SCP. In our study we estimated fasting serum C-peptide, urinary C-peptide and UCPCR in Type 2 Diabetes Mellitus (T2DM) subjects (n=113; male=74; female=39) with normal serum creatinine and urea levels. In all the cases of T2DM significant correlation were observed between serum C-peptide to urinary C-peptide and UCPCR. A significant correlation between serum C-Peptide and urinary C-Peptide in males and a significant correlation between serum C-Peptide and UCPCR in female subjects were also noticed. In T2DM subjects’ estimation of UCP in males and UCPCR in females may be used as simple, reproducible tests as predictors/biomarkers of endogenous insulin levels to assess status of beta cell functions.